Methods and results of a search for gravitational waves associated with gamma-ray bursts using the GEO 600, LIGO, and Virgo detectors - LIGO Scientific Collaboration (2014)
Paper producido por "The LIGO Scientific Collaboration and the Virgo Collaboration". (En el registro se mencionan solo algunos autores de las decenas de personas que participan).